Measuring the Changes in Copper Nanopowder Conductivity during Heating as a Method for Diagnosing its Thermal Stability; Key Engineering Materials; Vol. 769 : High Technology: Research and Applications (HTRA 2017) - Mostovshchikov A. V. Andrey Vladimirovich; Ilyin A. P. Aleksandr Petrovich; Zabrodina I. K. Irina Konstantinovna; Root L. O. Lyudmila Olegovna; Ismailov D. V. Daniar (2018, 2018)
Title screen